PASAL 54 KITAB UNDANG-UNDANG HUKUM ACARA PIDANA DALAM ELABORASI HUKUM PIDANA ISLAM - Diah Ratri Oktavriana; Nasiri Nasiri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
This research is a normative research. One of the fulfillment of human rights is justice in equalizing the position of every citizen before the law, as stated in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The right to equality before the law or what is commonly referred to as equality before the law is a principle that provides recognition and protection of human rights for every individual regardless of one's background. Therefore, it is true that Law Number 16 of 2011 concerning Legal Aid for People Who Are Less Capable to Guarantee Constitutional Rights of Citizens for Justice and Equality before the Law emerged. Legal aid is a legal service provided by advocates to the community seeking justice In the realm of criminal cases, the provision of legal assistance is described in Article 54 of the Criminal Procedure Code which explains that in the interests of defense, a suspect or defendant has the right to receive legal assistance from one or more legal advisers during the time and at each level of examination. The provision of legal assistance must be based on the principle of equality before the law as stated in the explanation of Law Number 8 of 1981 concerning Criminal Procedure Law. From the various analyzes that have been carried out, in the perspective of Islamic criminal law it can be concluded that the principle of equality before the law as described in Article 54 of the Criminal Procedure Code is equivalent to an order to provide legal aid which in Islamic criminal law is spelled out in Surah Al-Maidah verse 2 which states that as a fellow humans are ordered to help each other as a form of horizontal worship to fellow humans (habl minan-nas). In addition there are many more both in the Al Qur'an and the hadith of the prophet regarding the application of the principle of equality before the law.